Anthelmintic resistance, validation of famacha and effects of management practices in selected goat farms in Terengganu, Malaysia - Nor Azlina Abdul Aziz
A total of 230 goats from six goat farms in Marang, Kuala Berang and Setiu, Terengganu were chosen for this study. Distribution of anthemintic resistance is reported to be widespread in Malaysia. Therefore, it is important to evaluate the present anthelmintic resistance status of goats in Terengganu. Fecal samples were taken for fecal egg count (FEC). From 230 goats, 141 goats were chocen for detection of resistance by using Fecal Egg Count Reduction test, using levamisole, ivermectin, benzimidazole and closantel with each group having at least five goats including control. All farms had resistance towards benzimidazole and closantel while only two farms were still susceptible to levamisole and one farm had suspected resistance to ivermection. There were four out of six farms that had resistance to all anthelmintics tested. The strongyles which had developed anthemintic resistance were predominantly Haemonchus contortus followed by Trichostongylus spp. Results obtained from this study showed that anthelmintic resistance is escalating and the need for effective action is very important for the small ruminant industry.